Televisie en die kind - D.P. Van Vuuren (Communicare)
The South African Institute for Communication Research at the Human Sciences Research Council started its research programme on possible social effects of television in 1974, two years before the inception of this medium in South Africa. One of the major studies involves the effect of television on the general behaviour of school-going children. The present article comprises some of the most important results obtained so far in this research project.